The Influence of Profitability and Debt Rations Toward the Stock Return of Cosmetic Industry in Indonesia - Pandu Adi Cakranegara; Viesta Yoseva Dian Pramisti (Institute of Computer Science (IOCS), 2021)
The definite aim of this research is specifically for measuring the influence of profitability and debt ratios on stock return in the Indonesian cosmetic industry, both partially and simultaneously. There are five independent variables within this study examined by descriptive analysis, classical assumption test, multiple linear regression, and hypothesis testing. The research methodology uses a quantitative method that took from 2014-2019 quarterly financial report from five cosmetics companies listed in Indonesia Stock Exchange Adopting quantitative research and using secondary data, there will be 120 pieces of observation data from 5 samples from 2014-2019. The theoretical framework focused on Debt to Total Asset Ratio, Debt to Equity Ratio , Return on Asset , Earning per Share, Price Earning Ratio and the influence of financial ratios calculation in terms of EPS, DAR, DER, ROE, and PER on Stock Return in Indonesia’s Cosmetics Industry as the independent variables and Stock Return (Y) as the dependent variable. The findings of this research reveal that EPS, DAR, DER, ROA, and PER all have a significant impact on Stock returns. On the other hand, EPS and ROA do not significantly influence Stock returns. The other variables, DAR, DER, and PER, significantly influence Stock returns.